Philosophy of the human being - Maguigad, Rogelio B.; Singson, Jose Florante (C.M. Recto, Manila : Libro Filipino Enterprises, 2009)
Philosophy of the human being is not only challenging, but is also an intriguing subject to teach and learn. Aware of this, the authors had humbly prepared this textbook which was organized into outline topics so as to give the students quick efficient and effective ways of grasping this course in philosophy.
Chapter 1. introduction -- Chapter 2. ancient western philosophy -- Chapter 3. christian philosophy -- Chapter 4. modern western philosophy -- Chapter 5. existentialism -- Chapter 6. eastern philosophy part 1 -- Chapter 7. eastern philosophy part 2 -- Chapter 8. what is man -- Chapter 9. man and his knowledge -- Chapter 10. free will and concept of freedom -- Chapter 11. man and the state -- Chapter 12. philosophy of human rights -- Chapter 13. man and his questions -- Chapter 14. on the question of love -- Chapter 15. man and his destiny -- Chapter 16. women and gender in philosophy.
Includes bibliographical references.